Counterions control the self-assembly of structurally persistent micelles: Theoretical prediction and experimental observation of stabilization by sodium ions - Jäger, Christof; Hirsch, Andreas; Schade, Boris; Böttcher, Christoph; Clark, Timothy (Chemistry - A European Journal, 2009)
We show by molecular-dynamics (MD) simulations and cryotransmission electron microscopy (cryo-TEM) experiments that the size and form of structurally persistent micelles formed by the T-shaped amphiphile 1 are controlled by the counterions. The two techniques reveal that the micelles are specifically stabilized by sodium counterions relative to po-tassium ions. Both the simulations and the cryo-TEM experiments suggest that the micelles are stabilized by strongly conserved hydrated contact ion pairs with sodium counterions but not with potassium ions. We suggest that the TEM is observing local high density due to hydrated carboxylate/sodium ion pairs at the surface of the micelle. A high concentration of such structures is found in MD simulations with sodium counterions, but not with potassium. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.